New advances on the carbon isotope and rare earth elements chemostratigraphy of the late Ediacaran Tamengo Formation (Corumbá Group, Brazil) - Fernandes, Henrique Albuquerque; Boggiani, Paulo César; Viana, Aghata Zarelli; Caetano-Filho, Sergio [UNESP]; Pereira, Luiz Gustavo; Freitas, Bernardo Tavares; Hippertt, João Pedro; Morais, Luana [UNESP]; Trindade, Ricardo Ivan Ferreira (Elsevier, 2024)
The Tamengo Formation (Corumbá Group, midwest Brazil) is a carbonate-dominated succession of major importance to unravel the environmental and biological changes during the Ediacaran–Cambrian transition in Gondwana. Although it has been extensively studied in terms of sedimentology, isotope geochemistry, biostratigraphy, and geochronology, these studies are constrained to the Corumbá region. This work presents new sedimentological, C and O isotope chemostratigraphy, and rare earth elements (REE) plus yttrium (REY) data of four sections of the Tamengo Formation in the Serra da Bodoquena region, approximately 200 km south of Corumbá, discussing how these new data are related to the type sections. The sections present ooid grainstones, with hummocky, swaley, and wavy structures, interbedded with mudstones and shales, indicating deposition of fine particles by suspension fallout in-between periods of high-energy, with reworking by storm waves. The δ13Ccarb curves show positive plateaus with minor, short-lived negative excursions linked to facies variations, which are related to a large δ13Ccarb depth gradient in a redox-stratified water column. The REY profiles present middle REE (MREE)-bulge patterns and absent to slightly positive Ce anomalies, consistent with MREE adsorption onto Fe–Mn oxyhydroxides in the water column followed by release in pore waters. Subsequently, REY remobilization during anoxic diagenetic stages resulted in the MREE-bulge pattern and overprinted some of the original seawater REY features, including the Ce anomalies. The Tamengo Formation in the Serra da Bodoquena region represents a storm-dominated carbonate ramp, as previously interpreted for this unit in the Corumbá region. Nevertheless, there is a significant shift of 2 ‰ in the peaks of δ13Ccarb data between both localities, which may be related to differences in the overall sector of the carbonate ramp. There are also substantial variations in the δ13Ccarb record of the Tamengo Formation and other coeval Gondwana basins, such as the Nama and Itapucumi groups, with different peak values, which may be related to latitudinal differences on the inorganic carbon isotope composition or to the degree of basin restriction.
Keywords: Carbon isotopes; Chemostratigraphy; Corumbá Group; Rare earth elements; Tamengo Formation